Same duodenal neuroendocrine tumors, different endoscopic resection methods: a case report and literature review - Liu, Jinguo; Yu, Liangliang (Frontiers in Medicine, 2024)
Duodenal neuroendocrine tumors (NETs), comprising 2%-3% of all gastrointestinal NETs and 1%-3% of all duodenal tumors, are remarkably uncommon. In this report, we described a patient diagnosed with two submucosal tumors in the duodenal bulb.We employed two distinct endoscopic resection methods, including endoscopic submucosal dissection (ESD) and submucosal tunneling endoscopic resection (STER), to achieve en bloc resection of the lesions without complications. Pathological evaluation, involving hematoxylin-eosin staining and immunohistochemistry, confirmed the diagnosis of NET. Given the limited operative field and space in the duodenal bulb, STER proved to be a viable endoscopic resection technique.